AIDS-Associated Talaromyces marneffei Infection with Thoracic Spinal Cord Involvement Leading to Paraplegia: A Case Report and Literature Review - Guo Y; Song Y; Peng X; Zhou X; Zhou H; Xu L; Zhu B (Infection and Drug Resistance)
Yongzheng Guo,1 Ying Song,2 Xiaorong Peng,1 Xiaotang Zhou,1 Hengjun Zhou,3 Lijun Xu,1 Biao Zhu1 1The Department of Infectious Diseases, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, the First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 2The Department of Infectious Diseases, The Third People’s Hospital of Shenzhen and The Second Affiliated Hospital of Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 3Department of Neurosurgery, the First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Biao Zhu, Email zhubiao1207@zju.edu.cnBackground: Talaromyces marneffei is a common opportunistic infection in patients with acquired immune deficiency syndrome (AIDS) in South China. Spinal cord abscesses caused by T. marneffei are exceptionally rare and present with non-specific symptoms, which may result in delayed diagnosis and heightened adverse prognoses.Case Presentation: We report a case of a spinal cord abscess in a 30-year-old patient with AIDS that was caused by T. marneffei infection. The patient initially presented with T. marneffei septicemia and pleurisy. After initial antifungal treatment and combined antiretroviral therapy (cART), the patient’s condition temporarily improved. However, he discontinued the antifungal treatment against medical advice and subsequently developed paraplegia, T. marneffei meningitis, and related intracranial and thoracic spinal cord lesions. Neurosurgical resection of the spinal cord lesion, combined with continued cART and antifungal treatment, resulted in the intracranial mass in the cerebellum resolving on MRI, but the patient remained non-ambulatory and incontinent during the last follow-up in August 2024.Conclusion: In patients with spinal cord abscesses and a history of disseminated T. marneffei infection, especially those with AIDS, talaromycosis should be considered as a potential differential diagnosis. Comprehensive management, encompassing adherence to treatment plans and effective follow-up, is crucial for improving prognosis.Keywords: Talaromyces marneffei, HIV, fungi, abscess, spinal cord